Induction-Delivery Intervals between Misoprostol Alone and CombinedOxytocin-Misoprostol across Different Gestational Ages in PreEclampsia & Eclampsia (The Planet, 2024)
Introduction: Induction of labor in women with pre-eclampsia and eclampsia is a critical aspect of managing high-risk pregnancies, where timely delivery is often essential to prevent maternal and fetal complications. This study aims to compare the induction-delivery intervals between the use of misoprostol alone and in combination with oxytocin across different gestational ages in women with pre-eclampsia and eclampsia. Methods & Materials: This observational cross-sectional study was carried out in the Department of Gynaecology & Obstetrics at Dhaka Medical College Hospital, Dhaka, from July 2015 to December 2015. The study included 100 pre-eclampsia and eclampsia patients from the Eclampsia Ward at Dhaka Medical College, selected via purposive sampling. Data analysis was conducted using SPSS-19. Result: In the misoprostol-only group, the mean time from induction to delivery was 17.80 ± 4.17 hours for women with a gestational age of ≤36 weeks and 17.00 ± 4.15 hours for those >36 weeks, with no statistically significant difference between the two groups (p = 0.342). When oxytocin was added to misoprostol, the induction-delivery interval decreased to 8.30 ± 2.54 hours for ≤36 weeks and 7.68 ± 2.49 hours for >36 weeks, but again, the difference was not statistically significant (p = 0.224). Conclusion: Combining oxytocin with misoprostol shortens induction-delivery time compared to misoprostol alone, with no differences between gestational age groups. Further research is needed on maternal and neonatal outcomes.
Keywords: Induction-Delivery Intervals; Misoprostol; Gestational Ages; Pre-Eclampsia; Eclampsia